THE EFFECT OF USING FLASHCARD IN TEACHING VOCABULARY TO YOUNG LEARNERS : English - Alda Apriliani; Musdalifah Musdalifah; Annisa Kurnia Asri (JOEY: Journal of English Ibrahimy, 2025)
It was important to teach vocabulary to English young learners, since vocabulary is the starter to master language. However, it was more challenging to teach vocabulary to young learners compared to adult learners. Young learners have short attention span; thus, the teachers need to vary their learning media to make the students excited in learning the new language. One of the learning media that can be used is flashcard. Flashcard was one of media in teaching vocabulary that can help the students actively participate in the class. To find the effectiveness of flashcard, this study employed a pre-experimental research design with one group pre-test and post-test conducting 10 questions of multiple choice. Sampling technique used was total sampling, where all populations became the sample. The object of this research consisted of 36 children in the third grade of class G at MI Taqwa Bondowoso. The method used in this research was quantitative method design. The data were analyzed by using SPSS 21.0. The data showed the average score of pre tests was 65.00 and in post-test was 79.44. Furthermore, the result of t-test showed that the significant 2-tailed was 10.277. It could be concluded that there was significant effect in using a flashcard in teaching vocabulary to young learners.